Effects of exercise on cardiovascular performance in the elderly - Vigorito, Carlo; Giallauria, Francesco (Frontiers in Physiology, 2014)
Progressive Aging induces several structural and functional alterations in the cardiovascular system, among whom particularly important are a reduced number of myocardial cell and of increased interstitial collagen fibers, which result in impaired LV diastolic function. Even in the absence of cardiovascular disease, aging is strongly associated to a age-related reduced maximal aerobic capacity. This is due to a variety of physiological changes both at central and at peripheral level; among central factors, a reduced maximal heart rate (HR) response to exercise due to beta1 receptors down-regulation plays a major role; among peripheral factors, progressive aging is associated to peripheral muscle cell biochemical and functional changes including reduction of skeletal muscle cells, decrease of Myosin Heavy Chain (MHC) I and IIa muscle fibers and impaired muscle oxidative capacity